Розробка системи стеження за рухом сонця для підвищення ККД сонячних електростанцій - Кулик, Ярослав Анатолійович; Книш, Богдан Петрович; Шкуран, Михайло Володимирович; Черноволик, Олена Володимирівна (НТУ "ХПІ", 2017)
Обґрунтовано вибір типу реалізації структурної схеми для 2-х осьового поворотного механізму для сонячної панелі. Розроблено функціональну схему слідкування за рухом сонця через фотодатчики на цифровій елементній базі та програмне забезпечення на базі пристрою Arduino. Обґрунтоване розміщення фотодатчиків, яке дозволяє виконувати незалежне спостереження по 2-м осям. Розроблений пристрій збільшує вартість лише на 10 %, дозволяє підвищити ККД з 10-15 % до 40-55 % і має термін окупності 5-6 років.

Solar energy is environmentally friendly, independent of fossil sources, autonomous, does not require high cost for development and maintenance. The choice of the type of implementation of the structural scheme for the 2-hand rotary mechanism for the solar panel is substantiated. The functional scheme of monitoring the motion of the sun through photoconductors on a digital element base and software on the basis of the Arduino device, which controls 2 servo drives depending on the angle of inclination of the sun relative to the solar panel, is developed. Grounded posting of photo sensors, which allows you to perform independent observation on the 2nd axes. The developed device increases the cost by only 10%, allows you to increase the efficiency of 10-15% to 40-55% and has a payback period of 5-6 years when using the "green tariff".
Development of the solar tracking system to increase the efficiency of solar power plants
Keywords: сонячний трекер; фоторезистори; поворотний механізхм; сонячні панелі; фотодатчики